2017
DOI: 10.1039/c7tb02388j
|View full text |Cite
|
Sign up to set email alerts
|

Copper metal–organic polyhedra nanorods with high intrinsic peroxidase-like activity at physiological pH for bio-sensing

Abstract: Copper metal–organic polyhedra (Cu-MOP) nanorods exhibited high peroxidase-mimicking activity at a physiological pH value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…As the Cu/Cu x O/NC composite has the peroxidase-like activity, it can be used to detect H 2 O 2 or many other relative biomolecules which can generate H 2 O 2 , such as glucose, cholesterol, choline, xanthine, uric acid, and so on. In this work, glucose is chosen as a model molecule, and its concentration is determinated by Cu/Cu x O/NC mimic enzyme coupling with enzymatic oxidation of glucose.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Cu/Cu x O/NC composite has the peroxidase-like activity, it can be used to detect H 2 O 2 or many other relative biomolecules which can generate H 2 O 2 , such as glucose, cholesterol, choline, xanthine, uric acid, and so on. In this work, glucose is chosen as a model molecule, and its concentration is determinated by Cu/Cu x O/NC mimic enzyme coupling with enzymatic oxidation of glucose.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Table S3, the K m value of Cu/ Cu x O/NC with TMB (1.61 mM) is higher than that of HRP (0.434 mM), while the K m value with H 2 O 2 (0.82 mM) is much lower compared to HRP (3.7 mM). This further 48 cholesterol, 49 choline, 50 xanthine, 51 uric acid, 52 and so on. In this work, glucose is chosen as a model molecule, and its concentration is determinated by Cu/Cu x O/NC mimic enzyme coupling with enzymatic oxidation of glucose.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 89%
“…In another case, Ding group designed a Cu‐MOP nanorods which can catalyze the generation of strong chemiluminescence signals in the presence of luminol/H 2 O 2 . The oxidation of 2,2′‐azinobis‐(3‐ethylbenzthiazoline‐6‐sulphonate acid) (ABTS) by H 2 O 2 produces a green color reaction in a neutral pH solution . The color reaction generated by Cu‐MOP nanorod has been applied to develop a H 2 O 2 sensor, and furthermore is implemented to develop a glucose detection platform.…”
Section: Sensing and Bio‐imagingmentioning
confidence: 99%
“…The oxidation of 2,2'-azinobis-(3-ethylbenzthiazoline-6-sulphonate acid) (ABTS) by H 2 O 2 produces a green color reaction in a neutral pH solution. [44] The color reaction generated by Cu-MOP nanorod has been applied to develop a H 2 O 2 sensor, and furthermore is implemented to develop a glucose detection platform.…”
Section: Sensing and Bio-imagingmentioning
confidence: 99%
“…[4,7,8] Owing to their intriguing structures and their potential for a variety of applications, MOP have recently attracted considerable attention such as biomedicine, [9][10][11][12] catalysis, [7,[12][13][14] molecular sensing, [16] gas adsorption [17][18][19] and drug delivery. [20,21] Inspired by the superior performance of copper complexes in catalyzing oxidation ability in nature, our group have reported that Cu-MOP display excellent peroxidase mimicking enzyme activity in the physiological pH environment and were widely utilized in biosensing, [22] antibacterial [23] and cell protection [24] in recent years.…”
Section: Introductionmentioning
confidence: 99%